2021
DOI: 10.3390/ijms22073367
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential for Regulation of the Nuclear Factor Kappa-B Transcription Factor p65 to Prevent Cellular Senescence and Activation of Pro-Inflammatory in Mesenchymal Stem Cells

Abstract: Mesenchymal stem cells have an important potential in the treatment of age-related diseases. In the last years, small extracellular vesicles derived from these stem cells have been proposed as cell-free therapies. Cellular senescence and proinflammatory activation are involved in the loss of therapeutic capacity and in the phenomenon called inflamm-aging. The regulators of these two biological processes in mesenchymal stem cells are not well-known. In this study, we found that p65 is activated during cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…It has been reported that TA-MSC treatment of healthy donors with 20 ng/mL of TNF-α for 24 h induces SASP with increased expression of IL-6, IL-8, and monocyte chemotactic protein-1 (MCP-1) [172]. Even UC-MSCs treated with 5 ng/mL of TNF-α for three days have been used as a model of senescence [177]. This indicates the need to analyze in detail the effect of cytokine concentrations and exposure times on MSC functions.…”
Section: Alterations In Cell Morphology and Proliferationmentioning
confidence: 99%
“…It has been reported that TA-MSC treatment of healthy donors with 20 ng/mL of TNF-α for 24 h induces SASP with increased expression of IL-6, IL-8, and monocyte chemotactic protein-1 (MCP-1) [172]. Even UC-MSCs treated with 5 ng/mL of TNF-α for three days have been used as a model of senescence [177]. This indicates the need to analyze in detail the effect of cytokine concentrations and exposure times on MSC functions.…”
Section: Alterations In Cell Morphology and Proliferationmentioning
confidence: 99%
“…the downstream interferon signaling molecule IFITM3, which is located on the EV membrane and enriched during senescence (96). Induction of senescence by EVs may also depend on activation of NF-κ B in recipient cells (97). Furthermore, a deficiency in SIRT1 activity, which is decreased in multiple tissues during aging (98) and regulates longevity (71), can induce secretion of EVs or endothelial microparticles (56,99,100).…”
Section: Accepted Articlementioning
confidence: 99%
“…To optimize the clinical applications, the approaches used to develop biological products based on the molecular properties of MSCs and their mechanisms of action are being studied. Among these approaches, the paracrine function of MSCs via the secretome, which involves conditioned media (CM), EVs, and exosomes, is considered to be representative [ 5 , 9 , 13 , 14 , 15 , 16 , 17 ]. The CM derived from BM-MSCs and MB-MSCs have been shown to be capable of stimulating tube-like formation of human umbilical vein endothelial cells [ 5 ].…”
mentioning
confidence: 99%
“…In addition, the capacity to inhibit inflammation, which is consistent with the main actions described for EVs in general [ 15 , 18 ], has been observed in animal BPD models. Transmission of cellular senescence and proinflammatory activation between MSCs and their EVs are involved in the development of inflamm-aging, which is associated with the degeneration of organs and tissues during aging [ 16 ]. Mato-Basalo et al reported that treatment of senescent UC-MSCs with small inhibitors (e.g., JSH-23, MG-132, or curcumin) prevented cellular senescence and proinflammatory activation in MSCs, and paracrine and proinflammatory transmission by EVs through inhibition of the p65 pathway [ 16 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation